1992
DOI: 10.1159/000200887
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole and Omeprazole Have Similar Effects on Plasma Gastrin Levels, Enterochromaffin-Like Cells, Gastrin Cells and Somatostatin Cells in the Rat Stomach

Abstract: This study compares the effects of lansoprazole and omeprazole on the activation and proliferation of enterochromaffin-like (ECL) cells in the rat stomach. Lansoprazole was given orally once daily for 10 weeks in two doses, 135 and 200 μmol/kg. Omeprazole was given by the same regimen in a dose of 400 μmol/kg, which is equipotent in terms of acid inhibition to the higher lansoprazole dose. Lansoprazole (both doses) as well as omeprazole raised the plasma gastrin levels about 11 -fold 2 h after dosing and 8- to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…It can be assumed that the increasing number of CgA cells in the prepyloric mucosa means simultaneous increase of G cell count. Therefore, the results obtained in own studies may be regarded as a confirmation of the fact already known from papers by other authors (Chamouard et al, 1997;Graham et al, 1993;Kozlowski et al, 1993Kozlowski et al, , 1995Tzaneva & Julianov, 1999) and also obtained empirically (Lee et al, 1992) which point to participation of disturbances of interrelations between D and G cells in the pathomechanism of hypergastrinaemia that accompanies Helicobacter pylori colonization of gastric mucosa. It should be stressed that due to other causes, e.g.…”
Section: Assessment Of the Current Status Of Neuroendocrine And Immunsupporting
confidence: 86%
“…It can be assumed that the increasing number of CgA cells in the prepyloric mucosa means simultaneous increase of G cell count. Therefore, the results obtained in own studies may be regarded as a confirmation of the fact already known from papers by other authors (Chamouard et al, 1997;Graham et al, 1993;Kozlowski et al, 1993Kozlowski et al, , 1995Tzaneva & Julianov, 1999) and also obtained empirically (Lee et al, 1992) which point to participation of disturbances of interrelations between D and G cells in the pathomechanism of hypergastrinaemia that accompanies Helicobacter pylori colonization of gastric mucosa. It should be stressed that due to other causes, e.g.…”
Section: Assessment Of the Current Status Of Neuroendocrine And Immunsupporting
confidence: 86%
“…It has been observed that treatment with antiulcer agents such as H2R antagonists and PPIs induced hypergastrinemia and hypertrophy of the gastric mucosa in rodents (14,16). In the present study, serum gastrin levels, wet weights, and DNA contents of the stomach were assessed in H2R -/-mice.…”
Section: Figurementioning
confidence: 80%
“…Chronic application of acidinhibitory drugs elevates serum gastrin levels (14,16,30), and it has been suggested that the gastric pH influences the population of endocrine cells such as gastrinproducing G cells (30)(31)(32). The long-term elevation of gastric pH may increase G-cell density and then elevate serum gastrin levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations